2022
DOI: 10.1039/d2ta06383b
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Janus-structured ZnO@ZIF-8(-NH2)/cellulose nanofiber foam for highly efficient adsorption and photocatalysis-assisted desorption of tetracycline

Abstract: MOFs-based foam have potential applications in removing antibiotics from water. However, shaping MOFs into foam usually scarifies a portion of specific surface area, and thus reduces their adsorption properties, i.e.,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 106 publications
0
7
0
Order By: Relevance
“…Besides, the proportion of micropore contribution in N 0.1 /BDM-FDHCP (0.47) was slightly higher than that of BDM-DHCP (0.45). This is because the substitution of small-sized Py molecules led to the formation of smaller pores. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the proportion of micropore contribution in N 0.1 /BDM-FDHCP (0.47) was slightly higher than that of BDM-DHCP (0.45). This is because the substitution of small-sized Py molecules led to the formation of smaller pores. , …”
Section: Resultsmentioning
confidence: 99%
“…This is because the substitution of smallsized Py molecules led to the formation of smaller pores. 45,46 Furthermore, Figure S7 and Table S3 show the N 2 ad-/ desorption isotherms, pore size distribution, and corresponding textural parameters of BDM-SHCP and N x /BDM-FDHCP. As shown, N 0.1 /BDM-FHCP had the highest SSA (738 m 2 /g) and V total (0.66 cm 3 /g) among all N x /BDM-FDHCP samples.…”
Section: Textural Characterizationmentioning
confidence: 99%
“…After 10 cycles of operation, the initial absorption was reduced to 5% (Figure 11). 89 3.1.2. Catalytic Degradation of Organic Pollutants.…”
Section: Catalysismentioning
confidence: 99%
“…(b) Continuous cyclic adsorption results of C-ZnO0.5/ZAA foam via photocatalytic-assisted desorption (experiment condition: light intensity = 300 W xenon lamp, T = 25 °C) and conventional thermal solvent method (experiment condition: T = 80 °C, solvent = methanol). Reproduced with permission from ref . Copyright 2022, Royal Society of Chemistry.…”
Section: Applications Of Monolithic Mofsmentioning
confidence: 99%
“…1,2 The unique structure of ZIFs, with rich pore structure and high specific surface area and their resistance to chemical and thermal attack, 3 have led to their applications in various areas, such as air pollution control and adsorption. 4,5 Adsorption desulfurization (ADS) is considered a promising ultra-depth desulfurization technology to solve the inefficient use of fossil fuels and other serious environmental problems. Wu et al 6 found that ZIF-8 could remove thiophene by about 70%.…”
Section: Introductionmentioning
confidence: 99%